Market intelligence for guiding crop improvement: A systematic review of stakeholder preference studies in the rice sector in the Global South and beyond - Custodio, M.C.; Demont, M.; Steur, H. de (Wiley, 2023)
Improvement of crop varieties can be a powerful strategy for addressing food, nutrition, and climate challenges in the Global South if it is guided by market intelligence. We conducted a systematic literature review of stakeholder preference studies that aim at guiding crop improvement in rice, the Global South's most important staple food. We review behavioral indicators such as purchase intention, willingness to pay, acceptance, probability of adoption, and preference. Results from 106 studies reveal important gaps in terms of geographical and stakeholder representation: (1) Southcentral Asia is underrepresented and (2) studies focused either on upstream (farmers) or downstream (consumers) stakeholders along the value chain, while missing out on midstream actors (processors, traders). From the consumer studies, urban consumption zones are adequately represented as sources of end-market opportunities for farmers to tap into demand. Evidence suggests that consumer preferences for intrinsic attributes revolve around eating and cooking quality attributes (i.e., aroma, texture, swelling capacity, taste) and physical traits (i.e., whiteness, size and shape, proportion of broken grains). Evidence from farmer studies reveals that (1) preferences for agronomic attributes dominate and focus on yield, maturity, plant height, lodging tolerance, and tillering ability; (2) yield and early maturity were generally considered priority attributes and were often jointly considered as such; and (3) preferences for abiotic stress tolerance revolve around drought, submergence, and salinity. These insights can help refocus market intelligence research to aid crop improvement in addressing food, nutrition, and climate challenges in the Global South, which may be expanded globally.